New‐onset diabetes after renal transplantation in a patient with a novel HNF1B mutation. (21st February 2016) - Kanda, Shoichiro; Morisada, Naoya; Kaneko, Naoto; Yabuuchi, Tomoo; Nawashiro, Yuri; Tada, Norimasa; Nishiyama, Kei; Miyai, Takayuki; Sugawara, Noriko; Ishizuka, Kiyonobu; Chikamoto, Hiroko; Akioka, Yuko; et al.
Abstract: CAKUT are the most frequent causes of ESRD in children. Mutations in the gene encoding HNF1B, a transcription factor involved in organ development and maintenance, cause a multisystem disorder that includes CAKUT, diabetes, and liver dysfunction. Here, we describe the case of a patient with renal hypodysplasia who developed NODAT presenting with liver dysfunction. The NODAT was initially thought to be steroid and FK related. However, based on the patient's clinical features, including renal hypodysplasia and recurrent elevations of transaminase, screening for an HNF1B mutation was performed. Direct sequencing identified a novel splicing mutation of HNF1B, designated c.344 + 2T>C. Because CAKUT is the leading cause of ESRD in children and HNF1B mutations can cause both renal hypodysplasia and diabetes, HNF1B mutations may account for a portion of the cases of NODAT in pediatric patients who have undergone kidney transplantation. NODAT is a serious and major complication of solid organ transplantation and is associated with reduced graft survival. Therefore, for the appropriate management of kidney transplantation, screening for HNF1B mutations should be considered in pediatric patients with transplants caused by CAKUT who develop NODAT and show extra‐renal symptoms.